Sex hormones affect the pathogenesis and clinical characteristics of systemic lupus erythematosus - Kim, Ji-Won; Kim, Hyoun-Ah; Suh, Chang-Hee; Jung, Ju-Yang (Frontiers in Medicine, 2022)
Systemic lupus erythematosus (SLE) affects women more frequently than men, similar to the female predilection for other autoimmune diseases. Moreover, male patients with SLE exhibit different clinical features than female patients. Sex-associated differences in SLE required special considerations for disease management such as during pregnancy or hormone replacement therapy. Sex hormones, including estrogen and testosterone, are known to affect immune responses and autoimmunity. While estrogen and progesterone promote type-I immune response, testosterone enhances T-helper 1 response. Sex hormones also influence Toll-like receptor pathways, estrogen receptor signaling is involved in the activation and tolerance of immune cells. Further, the clinical features of SLE vary according to hormonal changes in female patients. Alterations in sex hormones during pregnancy can alter the disease activity of SLE, which is associated with pregnancy outcomes. Additionally, hormone replacement therapy may change SLE status. Sex hormones affect the pathogenesis, clinical features, and management of SLE; thus, understanding the occurrence and exacerbation of disease caused by sex hormones is necessary to improve its management.